2017
DOI: 10.1107/s205225251700700x
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic polarity formation in molecular crystals, composite materials and natural tissues

Abstract: This topical review summarizes the theoretical and experimental findings obtained over the last 20 years on the subject of growth-induced polarity formation driven by a Markov chain process. When entering the growing surface of a molecular crystal, an inorganic-organic composite or a natural tissue, the building blocks may undergo 180 orientational disorder. Driven by configurational entropy, faulted orientations can promote the conversion of a growing non-polar seed into an object showing polar domains. Simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…[23] This observation is supported by recent research on substi-tuted benzoic acids,w hich demonstrated that aromatic stacking-not hydrogen bonding-is akey step in nucleation and cluster growth in solution. [25] Polar crystals formed by dipolar molecules can build up substantial electric polarity,l eading to instability during crystal growth. The calculated molecular dipole moment of HCT in form Ii s 11.1 D( B3LYP/6-31G(d,p)), and the vector sum of these molecular dipoles gives m cell = 16.8 Da long the b axis.T he formation of polar domains in crystals is af undamental problem in current crystal-nucleation research.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[23] This observation is supported by recent research on substi-tuted benzoic acids,w hich demonstrated that aromatic stacking-not hydrogen bonding-is akey step in nucleation and cluster growth in solution. [25] Polar crystals formed by dipolar molecules can build up substantial electric polarity,l eading to instability during crystal growth. The calculated molecular dipole moment of HCT in form Ii s 11.1 D( B3LYP/6-31G(d,p)), and the vector sum of these molecular dipoles gives m cell = 16.8 Da long the b axis.T he formation of polar domains in crystals is af undamental problem in current crystal-nucleation research.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…The calculated molecular dipole moment of HCT in form I is 11.1 D (B3LYP/6‐31G(d,p)), and the vector sum of these molecular dipoles gives μ cell =16.8 D along the b axis. The formation of polar domains in crystals is a fundamental problem in current crystal‐nucleation research . Polar crystals formed by dipolar molecules can build up substantial electric polarity, leading to instability during crystal growth.…”
Section: Figurementioning
confidence: 99%
“…In previous investigations, the morphogenesis and characteristics of apatite–(CaF)–gelatin composites, which were synthesized within a gelatin gel with the double-diffusion technique, were described in detail from the nanometer to the micrometer scale. , Furthermore, in order to synthesize a material that is even more closely related to biological hard tissues, the influence of carbonate substitution in the apatite–(CaF) component of the composite material, which was grown within a gelatin gel, was investigated. The complex interactions of apatite and gelatine in composite materials were also probed by NMR. , The self-assembly of biomolecules in these synthetic materials such as apatite–(CaF)–gelatin composites was investigated by scanning pyroelectric microscopy (SPEM) and compared to that of natural tissues. , It was found that the grown apatite–(CaF)–gelatin composites revealed polarity, similar to in vivo tissues. In the case of noncentrosymmetric space groups (SGs), the polar axis in the crystal shows the direction along which the polar properties can be measured (incl.…”
Section: Introductionmentioning
confidence: 99%